Konsep Peran dan Pengaruh Organisasi Relawan TIK Dalam Pengembangan Literasi Digital: Analisis Tujuan, Kebutuhan, dan Rekrutmen - Fattah, Anwar; Wagimin, Wagimin; Hasan, Syahril (Puslitbang Akademi Relawan TIK Indonesia, 2025)
This study aims to explore the role and impact of Information and Communication Technology (ICT) volunteer organizations in digital literacy development, focusing on goal setting, needs identification, and the volunteer recruitment process. The research concept indicates that clear goal setting, which includes needs identification, consultation with stakeholders, and SMART goal development, significantly contributes to the effectiveness of digital literacy program implementation. Furthermore, identifying needs and challenges, including in-depth research and priority analysis, as well as program adjustments, influences the success of program monitoring and evaluation. The volunteer recruitment and selection process, which includes criteria selection, information dissemination, a rigorous selection process, and training and monitoring, plays a crucial role in ensuring the quality and commitment of volunteers, impacting the program evaluation outcomes. This research concept provides insights into how the relationship of ICT volunteer organizations can enhance the effectiveness of digital literacy programs through strategic planning, appropriate volunteer selection, and community-based program adjustments. The importance of feedback in the evaluation process is highlighted to improve and refine digital literacy programs in the future.